1984
DOI: 10.1002/hlca.19840670812
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Monoterpene Glucosides and Related Natural Products Part 51. Absolute Structures of Hydrangenosides A, B, C, D, E, F, and G. Novel Type Secoiridoid Glucosides from Two Hydrangea Plants

Abstract: SummaryFrom Hydrangea macrophylla var. macrophylla, four new secoiridoid glucosides, hydrangenosides A, B, C and D, were isolated, along with the known iridoid glucosides loganin, secologanin, secologanic acid and sweroside. Moreover, hydrangenosides E, F, and G, the glucosides of the same class, were isolated together with hydrangenosides C and D from Hydrangea scandens. Based on spectroscopic and chemical methods, the novel structures of the new glucosides consisting of secologanin and a shikimate-malonate-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
18
0

Year Published

1985
1985
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 13 publications
1
18
0
Order By: Relevance
“…10) To date, a number of bioactive compounds such as dihydroisocoumarins, secoiridoids, and stilbenes (hydrangenol, phyllodulcin, macrophylloside, and their glucosides) have been isolated from hydrangea plants. 11,12) Phyllodulcin has been identified as the compound responsible for the sweet taste of its infusion. 7) Hydrangea serrata (THUNB.)…”
Section: Introductionmentioning
confidence: 99%
“…10) To date, a number of bioactive compounds such as dihydroisocoumarins, secoiridoids, and stilbenes (hydrangenol, phyllodulcin, macrophylloside, and their glucosides) have been isolated from hydrangea plants. 11,12) Phyllodulcin has been identified as the compound responsible for the sweet taste of its infusion. 7) Hydrangea serrata (THUNB.)…”
Section: Introductionmentioning
confidence: 99%
“…Ser., a Saxifragaceae plant, is widely cultivated in many countries, including China and Japan. Known biologically active components from the genus Hydrangea are dihydroisocoumarins and their glycosides [1,2,3], iridoid glycosides, secoiridoid glycosides [4,5,6], flavonoid glycoside [7] and cyanoglycosides. Pharmacology research has demonstrated that these compounds possessed many biological functions, such as antidiabetic [8], antiallergic, antimicrobial activities [2] and protective effect against rat liver injury induced by D-galactosamine [9].…”
Section: Introductionmentioning
confidence: 99%
“…Hydrangea plants have a variety of bioactive compounds such as dihydroisocoumarins, secoiridoids, and stilbenes (hydrangenol, phyllodulcin, macrophylloside, and their glucosides) [5,6]. Among these compounds, we previously reported that hydrangenol, a dihydroisocoumarin, possesses potential protective effects on cell viability, production of procollagen type I, MMP-1, and pro-inflammatory cytokines [7].…”
Section: Introductionmentioning
confidence: 99%